2017
DOI: 10.1016/j.combustflame.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation and analysis of seven different chemical kinetic mechanisms for n-dodecane using a Rapid Compression-Expansion Machine

Abstract: Seven different chemical kinetic mechanisms for n-dodecane, two detailed and five reduced, have been evaluated under Engine Combustion Network (ECN) thermodynamic conditions by comparison to experimental measurements in a Rapid Compression-Expansion Machine (RCEM). The target ECN conditions are imposed at Top Dead Center (TDC), which cover a wide range of temperatures (from 850 K to 1000 K), oxygen molar fractions (0.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The early ignition prediction by the Yao mechanism has been attributed to increased accumulation of HO2 which is a key species in tracking first stage ignition [8]. It was found by [9] that reactions producing HCO which is a key species in producing HO2 were enhanced in the Yao mechanism leading to early ignition delay predictions. Additionally, predictions of the high temperature ignition stage which is promoted by the species H2O2 are also early for the Yao mechanism, as reactions relevant to the production of…”
Section: Flamelet Solutions Studymentioning
confidence: 99%
“…The early ignition prediction by the Yao mechanism has been attributed to increased accumulation of HO2 which is a key species in tracking first stage ignition [8]. It was found by [9] that reactions producing HCO which is a key species in producing HO2 were enhanced in the Yao mechanism leading to early ignition delay predictions. Additionally, predictions of the high temperature ignition stage which is promoted by the species H2O2 are also early for the Yao mechanism, as reactions relevant to the production of…”
Section: Flamelet Solutions Studymentioning
confidence: 99%
“…Concerning about previous kinetic work of the specific components of the surrogate, almost no kinetic study on TMCH oxidation was reported, in contrast to n-dodecane and NPB, with many studies available. In the last years, n-dodecane pyrolysis and oxidation was studied in detail [21][22][23][24][25][26][27] with providing also information on a kinetic model; furthermore, a few theoretical studies [28][29][30][31] were also published. At the same time, NPB was widely investigated in low pressure flame [32], auto-ignition [33][34][35], pyrolysis [36], and oxidation [37,38] experiments.…”
Section: Introductionmentioning
confidence: 99%
“…poor low-temperature chemistry description. [105] and Frassoldati et al [106] have performed well against experimental data obtained from RCM [99] and Spray A measurements [107,108].…”
Section: Chemical Mechanisms For N-dodecanementioning
confidence: 85%
“…As stated by Desantes et al [99], most n-dodecane mechanisms have an acceptable performance for engine simulations in terms of engine efficiency and fuel consumption but deviations from IDT experiments seem to be too high to accurately predict pollutant emissions. In particular, their capability to capture low-temperature chemistry is subject to even higher uncertainties compared to high-temperature ignition [99][100][101].…”
Section: Chemical Mechanisms For N-dodecanementioning
confidence: 93%
See 1 more Smart Citation